THE USE OF MANGROVE (Avicennia sp.) FRUIT EXTRACT AS A NATURAL ANTIBACTERIAL MATERIAL FOR THE TREATMENT OF DISEASES CAUSED BY Vibrio parahaemolyticus IN VANAME SHRIMP (Litopenaeus vannamei) - Dwi Arum Mufidah; Wardiyanto Wardiyanto; Rara Diantari (Jurusan Perikanan dan Kelautan, 2018)
Vaname shrimp (Litopenaeus vannamei) has high economical value as an export commodity However, there are obstacles that cause a decline in the level of shrimp exports in the world. One of the obstacle is shrimp disease which is treated using antibiotics. This method might ca-used pathogenic resistance and become a residue when consumed by humans. Avi-cennia sp. fruit extracthas benefits as natu-ral antibacterial ingredient that are safe to treat the shrimp which is infected by the Vibrio parahaemolyticus. In this study, shrimp is infected with Vibrio parahaemo-lyticus immersed using Avicennia sp. with a concentration of 300 mg L-1, 350 mg L-1, and 400 mg L-1 for 21 days plus the control treatment. The concentration of 400 mg L-1 showed better results compare to other con-centration on all observed parameters; fas-ter recovery time, higher survival rate and relative percent survival (RPS), also mild damage on hepatopancreas test. Keywords: Litopenaeus vannamei, antibiotics, Avicennia sp., fruit extract Vibrio parahaemolyticus